Kaji Eksperimental Torsi Statik Dan Dinamik Turbin Savonius Hidrokinetik Tipe Bach Tiga Sudu Dua Stagemenggunakan Plat Pengarah - Agus Saputra; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
hroughout human history great advances in culture have always been followed by increased energy consumption. Hydrokinetic energy can be used in Savonius turbines. The purpose of this research is to find out the static torque and dynamic torque produced from Savonius turbine type bach three blades by varying the first and second levels (15 cm: 15 cm, 17 cm: 13 cm and 20 cm: 10 cm) at the same total turbine height. The aspect ratio dimensions are 1.1, overlap ratio 0.2, rotor height (H) 0.3m, rotor diameter (D) 0.33 m, turbine diameter (d) 0.3 m, and with variations in water flow velocity ( V) 0.34 m / s and 0.51 m / s in the water tunnel. The two torques are obtained at rest (static torque) for each angle of the azimuth and moving conditions (dynamic torque) from no load and until it stops spinning. Based on the data obtained from the Savonius turbine type bach three-tiered blades using the directional blades produce α30˚: β10˚ angles on the 15/15 turbine get greater dynamic torque compared to research with turbines 17/13 or 20/13 that is equal to 0 , 3 Nm at a water velocity of 0.51 m⁄s, but compared to the results of the dynamic torque produced by the variation of the directional plate at an angle of α 30˚: β 10˚ and angle α 45˚: β 10˚ get smaller results that is 0.288 Nm and 0.252 Nm, the largest dynamic torque is 0.42 Nm and the static torque is 0, 528 Nm at a variation of 15 cm: 15 cm. From the results of the static torque, the Savonius turbine bach type three blades with variations of the directional plate at an angle of α60˚: β10˚ get a static torque greater than the variation of the directional plate at an angle of α 30˚: β 10˚, angle α 60˚: β 10˚ , which is equal to 0.3 Nm and 0.27 Nm, 0.264 Nm.Keywords: Savonius hydrokinetic turbine, guide blade, dynamic torque, static torque